New species of the genera Glyptothorax (Teleostei: Sisoridae) and Oreichthys (Teleostei: Cyprinidae) from Nagaland, Northeast India - Praveenraj, Jayasimhan; Vijayakrishnan, Balaji (Zootaxa, 2026)
Two new species of fishes are described from the tributaries of the Brahmaputra River in Nagaland, Northeast India. Glyptothorax sentimereni, described from the Dikhu River, is distinguished from congeners in having the following combination of characters: ventral surfaces of pectoral spine and first pelvic-fin ray with plicae, serrated posterior edge of dorsal-fin spine, thoracic adhesive apparatus completely encinctured by striae, length of dorsal-fin spine 13.7–16.1% SL, body depth at anus 17.1–19.6% SL, length of dorsal-fin base 12.0–13.1% SL, post-adipose distance 20.8–22.2% SL, head depth 16.5–17.0% SL and dorsal-to-adipose distance 21.8–23.5% SL. Oreichthys elianae, described from the Tsurang River, is distinguished from its congeners by a combination of characters that include 19+1 scales (with 5 pored scales) in longitudinal series, ½3/1/2½ scales in transverse row, 9 predorsal scales, 14–15 pores on cheek, a black spot on the caudal-fin base, and reddish fins.